Manfaat Media Pembelajaran Berbasis Aplikasi Kinemaster Terhadap Hasil Belajar IPA Siswa SDN 25 Tambangan - Wastriami, Wastriami; Mudinillah, Adam (STAI Asy-Syukriyyah, 2022)
The educational process at SDN 25 Tamabangan at the time of the COVID-19 pandemic experienced a decline due to the limitations of distance and time when delivering learning materials, so that at this time the role of technology and information was needed during the learning process because it had many advantages for the world of education. for a teacher the ability to master various kinds of learning media is very important, especially at SDN 25 Mining because the role of technology is very important in the learning process to be able to improve the learning process undertaken by students, because at this time the educators who teach at the elementary school cannot explain learning materials to students and only provide direct assignments without having to be explained first. The ability to master information technology in the current 4.0 revolution era is very important, by using this kinemaster application, it makes it easier for educators to provide materials that will be taught to students during the learning process. In this study, the aim is to be able to see whether the kinemaster-based learning media has benefits for student learning outcomes at SDN 25 Tambangan or not. the research method applied in the research process is a warkshop and is carried out jointly by all school officials at SDN 25 Tambangan. In the results of this study, it was found that the kinemaster application has many benefits that are felt by students in learning, for example, such as how students can know the teaching materials provided by educators.